Long-period grating based single-mode fiber to multi-core fiber pump coupler - Sousa, Liliana M. (2022)
We theoretically demonstrate a long-period grating (LPG) based single-mode fiber to multi-core fiber coupler. The coupling efficiency achieved was 24% of the input power, evenly distributed by all cores, using LPGs of length 4 cm.